2D WSe2 Flakes for Synergistic Modulation of Grain Growth and Charge Transfer in Tin‐Based Perovskite Solar Cells. Issue 11 (27th March 2021) - Wang, Tianyue; Zheng, Fangyuan; Tang, Guanqi; Cao, Jiupeng; You, Peng; Zhao, Jiong; Yan, Feng
Abstract: Tin (Sn)‐based perovskites with favorable optoelectronic properties and ideal bandgaps have emerged as promising alternatives to toxic lead (Pb)‐based perovskites for photovoltaic applications. However, it is challenging to obtain high‐quality Sn‐based perovskite films by solution process. Here, liquid‐exfoliated 2D transition‐metal dichalcogenides (i.e., MoS2, WS2, and WSe2 ) with smooth and defect‐free surfaces are applied as growth templates for spin‐coated FASnI3 perovskite films, leading to van der Waals epitaxial growth of perovskite grains with a growth orientation along (100). The authors find that WSe2 has better energy alignment with FASnI3 than MoS2 and WS2 and results in a cascade band structure in resultant perovskite solar cells (PSCs), which can facilitate hole extraction and suppress interfacial charge recombination in the devices. The WSe2 ‐modified PSCs show a power conversion efficiency up to 10.47%, which is among the highest efficiency of FASnI3 ‐based PSCs. The appealing solution phase epitaxial growth of FASnI3 perovskite on 2D WSe2 flakes is expected to find broad applications in optoelectronic devices. Abstract : Liquid‐exfoliated 2D transition‐metal dichalcogenides (MoS2, WS2, and WSe2 ) are introduced as growth templates for spin‐coated FASnI3 perovskite films, leading to van der Waals epitaxial growth of perovskite grains with a growth orientation along (100). The good energy alignment in the NiO x /WSe2 /FASnI3 structure facilitates hole extraction and suppresses interfacial charge recombination, leading to the best PCE of 10.47% for the PSC.